Three Characteristics of Cheetah Galloping Improve Running Performance Through Spinal Movement: A Modeling Study - Kamimura, Tomoya; Sato, Kaho; Aoi, Shinya; Higurashi, Yasuo; Wada, Naomi; Tsuchiya, Kazuo; Sano, Akihito; Matsuno, Fumitoshi (Frontiers in Bioengineering and Biotechnology, 2022)
Cheetahs are the fastest land animal. Their galloping shows three characteristics: small vertical movement of their center of mass, small whole-body pitching movement, and large spine bending movement. We hypothesize that these characteristics lead to enhanced gait performance in cheetahs, including higher gait speed. In this study, we used a simple model with a spine joint and torsional spring, which emulate the body flexibility, to verify our hypothesis from a dynamic perspective. Specifically, we numerically searched periodic solutions and evaluated what extent each solution shows the three characteristics. We then evaluated the gait performance and found that the solutions with the characteristics achieve high performances. This result supports our hypothesis. Furthermore, we revealed the mechanism for the high performances through the dynamics of the spine movement. These findings extend the current understanding of the dynamic mechanisms underlying high-speed locomotion in cheetahs.